Current and future perspectives for Helicobacter pylori treatment and management: From antibiotics to probiotics - Liang, Bing; Yuan, Yang; Peng, Xiao-Jin; Liu, Xin-Lin; Hu, Xiao-Kun; Xing, Dong-Ming (Frontiers in Cellular and Infection Microbiology, 2022)
Helicobacter pylori (H. pylori) is a Gram-negative anaerobic bacterium that colonizes the human stomach and is the leading cause of gastric diseases such as chronic gastritis and peptic ulcers, as well as the most definite and controllable risk factor for the development of gastric cancer. Currently, the regimen for H. pylori eradication has changed from triple to quadruple, the course of treatment has been extended, and the type and dose of antibiotics have been adjusted, with limited improvement in efficacy but gradually increasing side effects and repeated treatment failures in an increasing number of patients. In recent years, probiotics have become one of the most important tools for supporting intestinal health and immunity. Numerous in vitro studies, animal studies, and clinical observations have demonstrated that probiotics have the advantage of reducing side effects and increasing eradication rates in adjuvant anti-H. pylori therapy and are a valuable supplement to conventional therapy. However, many different types of probiotics are used as adjuncts against H. pylori, in various combinations, with different doses and timing, and the quality of clinical studies varies, making it difficult to standardize the results. In this paper, we focus on the risk, status, prevention, control, and treatment of H. pylori infection and review international consensus guidelines. We also summarize the available scientific evidence on using Limosilactobacillus reuteri (L. reuteri) as a critical probiotic for H. pylori treatment and discuss its clinical research and application from an evidence-based perspective.